Cultural Crisis During the Pandemic and Its Reflection in Georgian and American Print Media - Tsereteli , Asmat (Indonesian Journal Publisher, 2024)
The pandemic became the defining event of early 2020, impacting culture as well as all other areas of life. It emerged as the main architect, artist, director of silence, and dramatist of emptiness. It brought different cities around the world closer together and made them similar with empty streets and a slower pace of life. The pandemic placed new demands on many fields of art; it was a